THE MILITARY USE OF ANIMALS IN SOUTH AFRICA (1400-1881) - Alexander, McGill (Scientia Militaria - South African Journal of Military Studies, 2012)
The extent to which military operations depended on animals prior to the gradual mechanisation of armed forces which has taken place this century, is seldom fully appreciated by the soldier in a modern army. In South Africa, with its relatively short history profusely studded with belligerent actions ranging from internecine tribal squabbles through riots, rebellions, civil wars, invasions and conquests to international conflicts, animals have played a significant role in the conduct of military affairs. The varied topography and climate of the sub-continent has enabled animals to be utilized under many conditions which have taxed their capabilities in various fields to the utmost. It is the aim of this paper to examine the part played by animals in South African military annals, primarily in their combat and support roles, with brief reference to their ceremonial role. An effort will be made to assess their usefulness in each role at the time, and compare this to the modern application of animals in the South African Defence Force.